Leisure and Sport: What is Leisure? - Maurer, Suzanne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSES: Introduction to Sociology, Sociology of Sport, Sociology of Leisure. CONCEPT AREAS: Leisure theory, the social context of sport, self identity. TEACHING OBJECTIVE: To demonstrate how leisure theory applies to sport. To supply students with the opportunity to analyze and discuss the social contexts within which they equate leisure with sport.